DIGITAL FINANCIAL LITERACY, AND FINANCIAL TECHNOLOGY: CASE STUDIES OF FACULTY OF ECONOMICS UNIVERSITY 17 AUGUST 1945 SAMARINDA - Indrawati, Andi (Program Doktor Ilmu Ekonomi, 2021)
This research was conducted with the aim of knowing how much the level offinancial literacy in students of Economics, University of 17 August 1945Samarinda, and the authors wanted to know whether there was an influence of thelevel of financial literacy on interest in using Financial Technology products. Thistype of research is descriptive quantitative research using probability randomsampling techniques with student respondents majoring in managementaccounting study program. In this study, the data analysis used was descriptiveanalysis and multiple regression analysis using JASP. The results of this studyindicate that (1) the level of digital financial literacy has a significant effect onbuying interest in financial technology products, (2) which indicates that financialbehavior has no significant effect on buying interest. in financial technologyproducts.Keywords : Financial Literacy, Financial Behavior, Purchase Interest in FinancialTechnology Products